145k views
0 votes
The graph below shows a translation of preimage triangle vertex C to image triangle vertex C'.

What is the algebraic rule for this translation?
A. (x,y) = (x+6,9+2)
B. (x,y) → (x-6,y-2)
C. (x,y) → (x -6,y-6)
D. (x,y) → (x+2,x+10)

The graph below shows a translation of preimage triangle vertex C to image triangle-example-1

2 Answers

0 votes

Answer:

it is B

Explanation:

User Drowny
by
4.9k points
5 votes

Answer:

Option (B)

Explanation:

From the figure attached,

Triangle with vertex C' is a translated form of the triangle with vertex C.

Coordinates of pre-image C → (2 , 6)

Coordinates of the image C' → (-4, 4)

Rule followed from pre-image C to image C',

(2, 6) → (-4, 4)

(2, 6) → [(2 - 6), (6 - 2)]

(x, y) → [(x - 6), (y - 2)]

Therefore, rule given in option (B) is the answer.

User Sushovan Mandal
by
4.5k points